PELATIHAN PHARMAPRENEUR, PEMBUATAN KEMASAN, DAN PEMASARAN PRODUK MINUMAN KESEHATAN BERBAHAN KALAKAI Stenochlaena palustris SEBAGAI UMKM (INDUSTRI RUMAH TANGGA) - Hafiz Ramadhan; Dyera Forestryana; Ratna Restapaty; Rahmayanti Fitriah; Revita Saputri; Satrio Wibowo Rahmatullah (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Utilization of the potential of Kelakai (Stenochlaena palustris) as a health drink can be carried out and applied to prevent the spread of Covid-19. The purpose of this community service is to increase public interest in entrepreneurship, especially in groups of PKK women in Palam Village, Cempaka District, Banjarbaru. Entrepreneurship training was carried out in the production of processed healthy drinks from Kelakai including how to manufacture packaging and product marketing. The activity was held on November 8th, 2021, at the Palm Village Office Hall. The method of activity is through the presentation of entrepreneurship, how to make innovative, creative, and informative packaging, marketing practices by formulating strategies for marketing forms both directly and online. The activity was attended by 35 PKK women, lecturers, and students. The result obtained is an increase in partner knowledge about digital technology as an online marketing medium. Some partners have doubts about online marketing, but after participating in this activity, PKK women understand the basics of information and communication technology. This training attracted a group of PKK women in Palam Village, Cempaka District, Banjarbaru to develop processed products from Kalakai which were then marketed to create new UMKM in the form of Home Industries.